Aktivitas Fisik dan Tekanan Darah: Sebuah Studi Korelasional pada Siswa SMK di Yogyakarta - Maulida Akhlisa; Astry Axmalia; Ifa Suminingtyas; Tyas Handayani (PT. Promosi Kesehatan Media, 2026)
Background: Lack of physical activity in teenagers due to technological developments risks disrupting blood pressure stability, such as triggering hypertension. Preliminary studies at SMF Indonesia Yogyakarta Vocational School show that students' physical activity is still relatively light. This study aims to determine the relationship between physical activity and blood pressure in class XI students at SMK SMF Indonesia Yogyakarta. Method: This quantitative research uses a cross-sectional design. The research sample consisted of 43 respondents selected using purposive sampling technique. Physical activity was measured using the GPAQ (Global Physical Activity Questionnaire) questionnaire in MET units, while blood pressure was measured using a digital sphygmomanometer. Data analysis was carried out using the Kendall's Tau test because both variables are on an ordinal scale. Results and Discussion: The majority of respondents had a level of physical activity in the light category (58%) and blood pressure in the normal category (86%). The results of statistical tests show that there is a significant relationship between physical activity and blood pressure (p = 0.042) with the strength of the correlation being relatively weak (r = 0.298). Conclusion: There is a significant relationship between physical activity and blood pressure in class XI students of SMK SMF Indonesia Yogyakarta. Adolescents are advised to increase physical activity to maintain blood pressure stability.